High-strength gelatin / carbonic acid dihydrazide modified sodium alginate natural polymer hydrogel for 3D printing as well as preparation method and application of high-strength gelatin / carbonic acid dihydrazide modified sodium alginate natural polymer hydrogel
By mixing high-concentration gelatin with high-concentration dihydrazide modified sodium alginate and cross-linking treatment, a high-strength natural polymer hydrogel was prepared, which solved the problem of insufficient mechanical properties of natural hydrogels in the prior art, and achieved the combination of printability and excellent mechanical properties. It is suitable for hydrogel scaffolds in corneal regeneration.
Patent Information
- Application Number
- CN202311157728.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to develop an all-natural 3D printed hydrogel scaffold with both printability and excellent mechanical properties to simulate the complex multilayer structure of the natural cornea and apply it in corneal regeneration.
The mechanical properties of the hydrogel are enhanced by mixing high concentration gelatin with high concentration dihydrazide modified sodium alginate to be modified sodium alginate, and the extruded printed gelatin/carbonate dihydrazide modified sodium alginate is enhanced by cross-linking treatment of CaCl2 and EDC/NHS solutions.
The obtained high-strength natural polymer hydrogel has transparency and swelling similar to the natural corneal, has good biodegradability and biocompatibility, can serve as a reliable hydrogel stent in corneal regeneration, and has suturability during surgery.
Smart Images

Figure CN119587754A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical material science and regenerative medicine, and specifically relates to the preparation of a 3D printed high-strength natural polymer hydrogel and its application in the field of corneal regeneration. Background Art
[0002] The cornea is a transparent part with a certain curvature at the front end of the outer layer of the eyeball wall. The refractive power of the cornea accounts for 2 / 3 of the total refractive power of the eyeball and is crucial to vision. Many corneal diseases such as keratitis, erythematous keratitis or accidental physical trauma can damage the cornea and even cause vision loss. For these corneal injuries, corneal transplantation is the most common and most successful surgical method to restore corneal transparency and vision. However, limited transplant survival rate, disease infection, immune rejection and serious complications lead to a high failure rate of corneal transplantation, and the longer the transplant time, the higher the failure rate. Therefore, tissue-engineered corneal scaffolds have attracted widespread attention due to their flexibility and versatility, and are expected to become a therapeutic alternative to corneal transplantation.
[0003] The natural cornea has a complex multilayer structure, mainly composed of the epithelium, stroma, and endothelium. Traditional manufacturing methods cannot simulate the complex multilayer structure of the natural cornea, and can only obtain isotropic corneal scaffolds of a single component. As an emerging molding technology, 3D bioprinting can integrate different cells / active factors and biomaterials into a three-dimensional geometric structure by layer-by-layer deposition, and ultimately can flexibly customize specific corneal tissues. Various 3D bioprinted hydrogels that mimic the microenvironment of the natural cornea have been developed for corneal regeneration. These hydrogels are usually based on natural polymers with good biocompatibility and degradability, such as collagen, gelatin, hyaluronic acid, etc., which are the main components of the extracellular matrix of the natural cornea. However, these natural hydrogels often have the defect of insufficient mechanical properties and cannot withstand surgical sutures, which limits their reliability in clinical applications. Synthetic polymers reinforced natural polymer hydrogels is an alternative strategy. The mechanical properties of GelMA hydrogels reinforced with synthetic fibers (such as PCL or PECL) are significantly improved, and their tensile strength and elongation are even better than those of natural corneas. Therefore, these synthetic fiber-reinforced hydrogel scaffolds can be directly sutured surgically. However, these synthetic fibers cannot usually be directly introduced into 3D printing systems, and the synthetic polymer mesh in natural hydrogel scaffolds degrades very slowly in vivo. Therefore, it is necessary to develop an all-natural 3D printed hydrogel scaffold with biocompatibility, biodegradability and excellent mechanical properties for corneal regeneration. Summary of the invention
[0004] The purpose of the present invention is to develop a natural polymer hydrogel with both printability and excellent mechanical properties, as well as a preparation method and application thereof, such as for corneal regeneration, in view of the deficiencies in the prior art. First, a gelatin / sodium alginate modified with dihydrazide carbonate (Alg-CDH) natural polymer ink for extrusion printing was prepared by mixing high-concentration gelatin (Gel) with high-concentration sodium alginate modified with dihydrazide carbonate (Alg-CDH). The 3D-printed Gel / Alg-CDH hydrogel was then sequentially enhanced by soaking and cross-linking in CaCl2 solution and EDC / NHS solution, and a high-strength natural polymer hydrogel Gel-Alg-CDH-CaCl2 with excellent mechanical properties similar to natural corneal tissue was obtained. 2+ -EDC. Gel-Alg-CDH-Ca 2+ -EDC hydrogel has similar transparency and swelling degree as natural corneal tissue, good biodegradability and biocompatibility, and surgical sutureability given by excellent mechanical properties, and can be used as a hydrogel scaffold for corneal regeneration. In addition, different bioactive factors are introduced into Gel / Alg-CDH ink, and then a 3D-printed bioactive double-layer hydrogel scaffold can be prepared using a multi-nozzle printing system to meet the different needs of the corneal epithelium and stroma during the repair process, achieving the best corneal regeneration effect.
[0005] The technical purpose of the present invention is achieved through the following technical solutions.
[0006] A 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel and a preparation method thereof, wherein the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate is 3D printed and enhanced, wherein:
[0007] In the polymer ink of gelatin / carbonic acid dihydrazide modified sodium alginate, the mass ratio of gelatin to carbonate dihydrazide modified sodium alginate is (10-15):1, preferably (10-12):1; specifically, gelatin Gel is dissolved in deionized water at 37°C-45°C to obtain a Gel aqueous solution, and the mass volume percentage of gelatin is 20-40%. Carbonic acid dihydrazide modified sodium alginate (Alg-CDH) is dissolved in deionized water at 25°C-37°C to obtain an Alg-CDH aqueous solution, and the mass volume percentage of carbonate dihydrazide modified sodium alginate is 2-4%. Then the two are mixed evenly to obtain a polymer ink of gelatin / carbonic acid dihydrazide modified sodium alginate, recorded as Gel / Alg-CDH, wherein the mass volume percentage of gelatin is 10-20%, and the mass volume percentage of carbonate dihydrazide modified sodium alginate is 1-2%.
[0008] The 3D printing process of Gel / Alg-CDH ink was carried out using a 3D bioprinter with a low-temperature deposition platform. The corresponding G-code file was obtained from the model designed by CAD / CAM software or the 3D model reconstructed by Micro-C through CuraEngine slicing software to guide the layer-by-layer printing protocol to build the designed structure. Printing was performed according to the following scheme: the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate was loaded into the extrusion printer barrel immediately after preparation, incubated at a temperature of 32℃-37℃, and then extruded through a 27G-22G printing needle at an air pressure of 0.1-0.5MPa, and deposited on a platform of 10℃-25℃ according to the set slicing model. Finally, the printed hydrogel structure was transferred to a refrigerator at 4℃ to wait for subsequent enhancement treatment.
[0009] The 3D printed hydrogel structure was reinforced: First, the printed hydrogel was immersed in a CaCl2 aqueous solution for 5-10 minutes to achieve the CaCl2 concentration of the alginate component in the hydrogel. 2+ The cross-linked hydrogel was recorded as Gel-Alg-CDH-Ca 2+ Then, Gel-Alg-CDH-Ca was washed with deionized water. 2+ After that, it was immersed in EDC / NHS solution for 1-10 min to obtain suitable chemical crosslinking. The physicochemical synergistic hydrogel after this sequential enhancement strategy was recorded as Gel-Alg-CDH-Ca 2+ -EDC, i.e., the 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel of the present invention.
[0010] The above-mentioned polymer hydrogel is used in corneal regeneration (i.e., the above-mentioned polymer hydrogel is used to prepare the cornea or used as a material for preparing the cornea), and growth factors and histone deacetylase inhibitors that promote corneal re-epithelialization are respectively added to the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate to obtain two printing bio-inks, and a 3D printed bioactive double-layer hydrogel scaffold is obtained by printing layer by layer through a multi-nozzle printing system, and then the above-mentioned enhancement treatment is performed to obtain a 3D printed bioactive double-layer hydrogel scaffold used in corneal transplantation surgery.
[0011] Among them, growth factors that promote corneal re-epithelialization include epidermal growth factor (EGF), keratinocyte growth factor (KGF) or fibroblast growth factor (FGF).
[0012] The histone deacetylase inhibitors are trichostatin A (TSA) or vorinostat (SAHA).
[0013] Growth factors that promote corneal re-epithelialization and histone deacetylase inhibitors are added to the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate, respectively. The concentration of growth factors that promote corneal re-epithelialization is 1-5 μg / ml, and the concentration of histone deacetylase inhibitor is 1-5 μmol / L.
[0014] Compared with the prior art, the 3D printed high-strength natural polymer hydrogel system of the present invention has both 3D printing performance and excellent mechanical properties, as well as the excellent biocompatibility and biodegradability of the natural polymer itself. The physicochemical properties of the hydrogel are similar to those of the natural cornea, and the excellent mechanical properties give it surgical sutureability, and it can be used as a reliable corneal regeneration scaffold. In particular, the design of the 3D printed bioactive double-layer hydrogel scaffold can promote corneal re-epithelialization and inhibit corneal scar formation, respectively, to meet the different needs of the epithelium and stromal layer during corneal regeneration. The preparation method is simple to operate, and the prepared hydrogel scaffold and the bioactive double-layer hydrogel scaffold can effectively promote corneal regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a graph showing the rheological properties of Gel / Alg-CDH inks with different ratios (1).
[0016] Figure 2 This is a graph showing the rheological properties test results of Gel / Alg-CDH inks with different ratios (2).
[0017] Figure 3 This is a graph showing the rheological properties of Gel / Alg-CDH inks with different ratios (3).
[0018] Figure 4 The following are photos showing the printability of Gel / Alg-CDH inks with different ratios. Scale bar: 750 μm.
[0019] Figure 5 It is a bar graph showing the semi-quantitative analysis results of the printability of Gel / Alg-CDH inks with different ratios.
[0020] Figure 6 This is a schematic photograph of the curvature corneal structure printed in suspension using the Gel / Alg-CDH-20-2.0 ink of the present invention.
[0021] Figure 7 This is a graph showing the mechanical properties test results of Gel / Alg-CDH-20-2.0 hydrogel after sequential reinforcement treatment (1).
[0022] Figure 8 This is a graph showing the mechanical properties test results of Gel / Alg-CDH-20-2.0 hydrogel after sequential reinforcement treatment (2).
[0023] Fig. 9 This is a curve diagram of the mechanical properties test results of Gel / Alg-CDH-20-2.0 hydrogel after sequential reinforcement treatment (3).
[0024] Fig.10 This is a schematic photograph of the mechanical properties test results of Gel / Alg-CDH-20-2.0 hydrogel after sequential reinforcement treatment.
[0025] Fig.11 The Gel-Alg-CDH-Ca 2+ - Transparency test results of EDC hydrogel.
[0026] Fig.12 The Gel-Alg-CDH-Ca 2+ -Swelling rate test results of EDC hydrogel.
[0027] Fig.13 The Gel-Alg-CDH-Ca 2+ - Curve graph of the enzymatic degradation test results of EDC hydrogel.
[0028] Fig.14 The Gel-Alg-CDH-Ca 2+ -Photo showing the suture retention ability test results of EDC hydrogel.
[0029] Fig.15 The Gel-Alg-CDH-Ca 2+ -Graph showing the suture retention ability test results of EDC hydrogel.
[0030] Fig.16 The Gel-Alg-CDH-Ca 2+ - Bar graph of suture retention test results of EDC hydrogel.
[0031] Fig.17 This is a schematic photo of the preparation of rhEGF / TSA bioactive double-layer hydrogel scaffold using a multi-nozzle printing system. Scale: 1 mm.
[0032] Fig.18 The present invention is a slit lamp observation and AS-OCT photograph of the rhEGF / TSA double-layer hydrogel scaffold after being applied to the anterior lamellae transplantation of the rabbit cornea.
[0033] Fig.19 This is a histological section analysis photograph of the rhEGF / TSA double-layer hydrogel scaffold of the present invention applied to the anterior lamellae of the rabbit cornea for the 14th day after transplantation, with a scale of 100 μm. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but these examples are not intended to limit the present invention.
[0035]
[0036]
[0037] The synthesis of carbonate dihydrazide modified sodium alginate (Alg-CDH) used in the present invention is carried out according to the following steps and can be specifically referred to (Extracellular matrix (ECM)-inspired high-strength gelatin-alginate based hydrogels for bone repair, Biomater. Sci., 2023, 11, 2877): First, 2.0g of alginate is added to 200ml of deionized water and dissolved at room temperature. Then 360mg of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), 540mg of 1-hydroxybenzotriazole (HOBT) and 360mg of carbonate dihydrazide (CDH) are added in sequence and reacted at room temperature for 48h. Finally, the reaction solution is transferred to a dialysis bag, dialyzed in deionized water for 3 days, and freeze-dried to obtain the Alg-CDH product.
[0038] First, the preparation of 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel was carried out according to the following steps:
[0039] Step 1, dissolving gelatin in deionized water at 45°C to obtain 20 w / v%, 30 w / v% and 40 w / v% gelatin aqueous solutions, wherein the mass volume percentage of 0.1 g gelatin and 1 ml deionized water is 10%, i.e. 10 w / v%.
[0040] Alg-CDH was dissolved in deionized water at 37°C to obtain 2 w / v%, 3 w / v% and 4 w / v% Alg-CDH aqueous solutions, wherein the mass volume percentage of 0.1 g Alg-CDH and 1 ml deionized water was 10%, i.e., 10 w / v%.
[0041] Equal volumes of 20 w / v% Gel aqueous solution and 2 w / v% Alg-CDH aqueous solution, 30 w / v% Gel aqueous solution and 3 w / v% Alg-CDH aqueous solution, and 40 w / v% Gel aqueous solution and 4 w / v% Alg-CDH aqueous solution were mixed evenly, and the resulting inks were named Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5, and Gel / Alg-CDH-20-2.0, respectively.
[0042] Step 2, 3D printing of Gel / Alg-CDH ink on a 3D bioprinter with a cryo-deposition platform ( The corresponding G-code files were obtained from the models designed by CAD / CAM software or the 3D models reconstructed by Micro-C by using CuraEngine slicing software to guide the layer-by-layer printing protocol to build the designed structure.
[0043] Specifically, the Gel / Alg-CDH ink obtained in step 1 was loaded into a 5 ml measuring cylinder and the temperature was controlled at 34°C (Gel / Alg-CDH-10-1.0), 35°C (Gel / Alg-CDH-15-1.5), and 36°C (Gel / Alg-CDH-20-2.0). After calibrating the platform and nozzle of the 3D bioprinter, appropriate pressure (0.1-0.5 MPa) was applied to make the ink flow through a 23G needle with an inner diameter of 0.34 mm. The printed hydrogel structure was deposited on the platform at 20°C. Finally, the printed hydrogel structure was transferred to a refrigerator at 4°C for subsequent enhancement.
[0044] Step 3: In order to improve the mechanical properties of the hydrogel, the hydrogel structure printed in step 2 was subjected to sequential reinforcement treatment. First, the printed hydrogel was immersed in a 50 mM CaCl2 aqueous solution for 10 minutes to achieve CaCl2 of the alginate component. 2+ The cross-linked hydrogel was recorded as Gel / Alg-CDH-Ca 2+ Then, the Gel / Alg-CDH-Ca was washed with deionized water. 2+ , and immersed in 10mM EDC / NHS aqueous solution for 1, 3, 5 and 10 minutes respectively to achieve different degrees of chemical crosslinking (the subsequent test samples were selected as hydrogel samples with an optimized immersion time of 3min). Finally, the physicochemical synergistic hydrogel after the sequential enhancement strategy was recorded as Gel-Alg-CDH-Ca 2+ -EDC.
[0045] The dynamic rheological behavior of Gel / Alg-CDH ink was tested using a rheometer (MCR302, Anton Paar) with a temperature control system. Figure 1 As shown in Figure 2, Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5 and Gel / Alg-CDH-20-2.0 all undergo gel-sol transition as the temperature increases, and their transition temperatures are 36°C, 38°C and 41°C, respectively. Figure 2 As shown in Figure 2, the viscosity of Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5, and Gel / Alg-CDH-20-2.0 also decreases with increasing temperature, with the most significant change at the gel-sol transition point. Figure 3 As shown in the figure, Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5 and Gel / Alg-CDH-20-2.0 also exhibit obvious shear thinning behavior near their respective gel-sol transition temperatures. Therefore, these temperature-sensitive Gel / Alg-CDH inks can be extruded at relatively high temperatures and deposited at relatively low temperatures, thereby realizing the 3D printing process.
[0046] The 3D printing performance of Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5, and Gel / Alg-CDH-20-2.0 inks was demonstrated using a 3D bioprinter. Figure 4 As shown in the figure, Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5 and Gel / Alg-CDH-20-2.0 inks exhibit good printability at 34°C, 35°C and 36°C, respectively, and the printed grid structures are clear and neat with high resolution. Figure 5 As shown in the figure, at temperatures close to body temperature, the printability index Pr of Gel / Alg-CDH-10-1.0, Gel / Alg-CDH-15-1.5 and Gel / Alg-CDH-20-2.0 inks are all close to 1, which means that these inks have good printability near body temperature and can be used as bio-inks. Figure 6 As shown, corneal structures with curvature can be printed with the help of the suspension printing system Gel / Alg-CDH-20-2.0 ink.
[0047] The mechanical properties of the printed Gel / Alg-CDH hydrogel after sequential reinforcement treatment were tested. Figure 7 , 8 As shown in Figure 9, the Gel-Alg-CDH-20-2.0-Ca 2+-EDC hydrogel exhibits a J-type stress-strain curve similar to the mechanical properties of natural cornea, and has excellent mechanical properties with a tensile strength of more than 1MPa and an elongation at break of more than 180%. Fig.10 As shown, Gel-Alg-CDH-20-2.0-Ca 2 + -EDC hydrogel can withstand large tensile and torsional deformations, and a 300 μm thick hydrogel can withstand a load of 50 g.
[0048] Continue to test the Gel-Alg-CDH-10-1.0-Ca 2+ -EDC, Gel-Alg-CDH-15-1.5-Ca 2+ -EDC and Gel-Alg-CDH-20-2.0-Ca 2+ -The physicochemical properties of EDC hydrogels, including transparency, swelling rate, enzymatic degradability and suture retention ability. Fig.11 As shown, Gel-Alg-CDH-10-1.0-Ca 2+ -EDC (shown as 1 in the embedded figure) has low transparency, and its transmittance in the visible light region does not exceed 30%. 2+ -EDC (shown in Figure 2) and Gel-Alg-CDH-20-2.0-Ca 2+ -EDC(Embedded Figure 3 ) has a transmittance of about 80% in the visible light region, which can meet the use requirements of corneal stents. Fig.12 As shown, Gel-Alg-CDH-10-1.0-Ca 2+ -EDC, Gel-Alg-CDH-15-1.5-Ca 2+ -EDC and Gel-Alg-CDH-20-2.0-Ca 2+ -EDC hydrogels basically reached swelling equilibrium after being immersed in PBS at 37°C for 24 hours, and all had low swelling rates (6.6±2.5%, 14.9±4.7% and 13.8±7.1%, respectively), which prevented the hydrogel scaffold from causing great pressure on the surrounding eye tissues due to excessive swelling after implantation. Fig.13 As shown, Gel-Alg-CDH-10-1.0-Ca 2+ -EDC, Gel-Alg-CDH-15-1.5-Ca 2+ -EDC and Gel-Alg-CDH-20-2.0-Ca 2+-EDC hydrogels all have rapid enzymatic degradation behavior, and they are completely degraded within 72 h when immersed in 0.1 U / mL collagenase A PBS solution at 37 °C.
[0049] In addition, Gel-Alg-CDH-10-1.0-Ca 2+ -EDC, Gel-Alg-CDH-15-1.5-Ca 2+ -EDC and Gel-Alg-CDH-20-2.0-Ca 2+ -Suture retention properties of EDC hydrogel. Fig.15 and 16 As shown (in Fig.16 In the figure, two columns form a group, the left column corresponds to the load, and the right column corresponds to the displacement). Compared with the GelMA hydrogel (concentration of 20%) commonly used in the field of regenerative medicine, Gel-Alg-CDH-10-1.0-Ca 2+ -EDC, Gel-Alg-CDH-15-1.5-Ca 2+ -EDC and Gel-Alg-CDH-20-2.0-Ca 2+ -EDC hydrogels have significantly higher suture retention capacity. The 20% GelMA hydrogel has almost no suture retention capacity, and the suture can pass through the hydrogel under a very small load (0.025N) with a displacement of only about 1mm. In contrast, Gel-Alg-CDH-10-1.0-Ca 2+ -EDC can withstand a load of 0.038N and a displacement of 3.2mm, Gel-Alg-CDH-15-1.5-Ca 2+ -EDC can withstand a load of 0.053N and a displacement of 2.7mm, while Gel-Alg-CDH-20-2.0-Ca 2+ -EDC can withstand a load of 0.071N and a displacement of 3.5mm. Gel-Alg-CDH-20-2.0-Ca 2+ -EDC has a maximum load and maximum displacement that are approximately 3 times that of 20% GelMA hydrogel, which means that it can withstand greater perturbations without rupture during surgical suturing. Fig.14 As shown, Gel-Alg-CDH-20-2.0-Ca 2+ -EDC hydrogel was successfully sutured to the surface of an in vitro skin model.
[0050] The Gel / Alg-CDH-20-2.0 of the present invention was selected as a benchmark, and recombinant human epidermal growth factor (rhEGF) and trichostatin A (TSA) were added thereto to prepare a 3D printed rhEGF / TSA bioactive double-layer hydrogel scaffold for corneal regeneration, according to the following steps:
[0051] Step 1: Recombinant human epidermal growth factor (rhEGF) and trichostatin A (TSA) were introduced into Gel / Alg-CDH-20-2.0 ink, respectively, to prepare uniform bio-ink A (rhEGF concentration: 2 μg / ml) and bio-ink B (TSA concentration: 5 μmol / L).
[0052] Step 2: Use bio-ink A and bio-ink B to print layer by layer in a multi-nozzle printing system to obtain the rhEGF / TSA double-layer hydrogel scaffold.
[0053] Step 3: The rhEGF / TSA double-layer hydrogel scaffold was sequentially enhanced by soaking it in a 50 mM CaCl2 aqueous solution and a 10 mM EDC / NHS aqueous solution in accordance with the previous scheme to achieve chemical cross-linking and enhancement treatment.
[0054] Step 4: Application of rhEGF / TSA double-layer hydrogel scaffold in rabbit anterior corneal lamellar transplantation surgery.
[0055] Attached Fig.17 Figure a shows the layer-by-layer printing process of bio-ink A and bio-ink B in a multi-nozzle printing system. Fig.17 Figure b shows the printed rhEGF / TSA double-layer hydrogel scaffold, attached Fig.17 c shows the rhEGF / TSA double-layer hydrogel scaffold after sequential enhancement treatment.
[0056] As shown in the table below, by changing the printing parameters, the thickness of the double-layer hydrogel scaffold can be adjusted between 250 μm and 400 μm, and this thickness range can adapt to different corneal injury depths.
[0057]
[0058] Attached Fig.18Slit lamp photos and AS-OCT photos show the repair effect of rhEGF / TSA double-layer hydrogel scaffold applied to rabbit corneal anterior lamellar transplantation. Compared with the control group without hydrogel scaffold transplantation (marked control in the figure), on the 7th day after surgery, the thickness of the central stromal layer in the corneal defect area of the two hydrogel scaffold implantation groups was significantly thicker than that of the central stromal layer in the corneal defect area of the control group. On the 14th day after surgery, the stromal thickness of the corneal defect area of the control group was still significantly lower than that of the surrounding tissue, while the corneal morphology of the hydrogel scaffold transplantation group of the present invention (marked Hydrogel in the figure) and the rhEGF / TSA double-layer hydrogel scaffold transplantation group (marked EGF / TSA-Hydrogel in the figure) was basically consistent with the surrounding normal tissue, and its stromal thickness was significantly higher than that of the control group, close to the normal corneal stroma, indicating that the implantation of the two hydrogel scaffolds effectively promoted stromal regeneration. In addition, new epithelial layers appeared in both hydrogel scaffold implantation groups on the 14th day after surgery, achieving re-epithelialization.
[0059] Attached Fig.19 The histological section analysis of corneal repair in each group on the 14th day is shown. H&E staining images show that the cornea of the rhEGF / TSA double-layer hydrogel scaffold transplantation group has a better repair effect, and its epithelial and stromal morphologies are similar to those of the normal cornea group. The corneal stroma of the control group showed obvious disordered collagen fiber structure, which means that severe scar tissue has formed (red arrow area), while the corneal new stroma of the pure hydrogel group did not show obvious disordered collagen fiber structure, but scar-like tissue with dark and elongated cell nuclei appeared (red arrow area). Only the new stroma of the rhEGF / TSA double-layer hydrogel scaffold transplantation group formed a parallel arranged collagen sheet structure similar to the natural corneal stroma. These results prove that Gel-Alg-CDH-20-2.0-Ca 2+ -EDC hydrogel scaffold and rhEGF / TSA bioactive double-layer hydrogel scaffold can effectively support corneal regeneration. In particular, rhEGF / TSA bioactive double-layer hydrogel scaffold has the effect of promoting corneal re-epithelialization and inhibiting corneal scarring, which can achieve better repair effect.
[0060] According to the content of the present invention, the process parameters are adjusted to achieve the preparation of 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate-based hydrogels and the design of bioactive double-layer hydrogels, which are tested to show performance that is basically consistent with the present invention. The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be done by other technicians in this field without spending creative labor falls within the scope of protection of the present invention.
Claims
1. A 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel, characterized in that: The polymer ink of sodium alginate modified with gelatin / dihydrazide carbonate is obtained by 3D printing and enhancement treatment, wherein: In the gelatin / carbonic acid dihydrazide modified sodium alginate polymer ink, the mass ratio of gelatin to carbonate dihydrazide modified sodium alginate is (10-15):1, the mass volume percentage of gelatin is 10-20%, and the mass volume percentage of carbonate dihydrazide modified sodium alginate is 1-2%; A 3D bioprinter with a low-temperature deposition platform was used to 3D print the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate, and the printed hydrogel was reinforced by soaking it in a calcium chloride aqueous solution and an EDC / NHS aqueous solution in sequence to achieve cross-linking.
2. A 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel according to claim 1, characterized in that: In the gelatin / dihydrazide carbonate modified sodium alginate polymer ink, the mass ratio of gelatin to dihydrazide carbonate modified sodium alginate is (10-12):
1.
3. A method for preparing a 3D printed high-strength gelatin / dihydrazide carbonate-modified sodium alginate natural polymer hydrogel, characterized in that: The polymer ink of sodium alginate modified with gelatin / dihydrazide carbonate is obtained by 3D printing and enhancement treatment, wherein: In the gelatin / carbonic acid dihydrazide modified sodium alginate polymer ink, the mass ratio of gelatin to carbonate dihydrazide modified sodium alginate is (10-15):1, the mass volume percentage of gelatin is 10-20%, and the mass volume percentage of carbonate dihydrazide modified sodium alginate is 1-2%; A 3D bioprinter with a low-temperature deposition platform was used to 3D print the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate, and the printed hydrogel was reinforced by soaking it in a calcium chloride aqueous solution and an EDC / NHS aqueous solution in sequence to achieve cross-linking.
4. The method for preparing a 3D printed high-strength gelatin / dihydrazide carbonate-modified sodium alginate natural polymer hydrogel according to claim 3, characterized in that: In the gelatin / dihydrazide carbonate modified sodium alginate polymer ink, the mass ratio of gelatin to dihydrazide carbonate modified sodium alginate is (10-12):
1.
5. The method for preparing a 3D printed high-strength gelatin / dihydrazide carbonate-modified sodium alginate natural polymer hydrogel according to claim 3, characterized in that: Gelatin is dissolved in deionized water at 37-45°C to obtain a gelatin aqueous solution, wherein the mass volume percentage of the gelatin is 20-40%; sodium alginate modified with dihydrazide carbonate is dissolved in deionized water at 25-37°C to obtain an aqueous solution, and then the two are evenly mixed to obtain a gelatin / dihydrazide carbonate modified sodium alginate polymer ink.
6. The method for preparing a 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel according to claim 3, characterized in that: Printing was performed according to the following scheme: the polymer ink of gelatin / dihydrazide carbonate-modified sodium alginate was loaded into the barrel of the extrusion printer immediately after preparation, incubated at a temperature of 32°C-37°C, and then extruded through a 27G-22G printing needle at an air pressure of 0.1-0.5MPa, and deposited on a platform at 10°C-25°C according to the set slicing model, and the printed hydrogel was transferred to a refrigerator at 4°C for storage.
7. The method for preparing a 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel according to claim 3, characterized in that: Soak the printed hydrogel in a CaCl2 aqueous solution for 5-10 minutes to achieve CaCl2 2+ The cross-linked hydrogel was recorded as Gel-Alg-CDH-Ca 2+ ; Then, Gel-Alg-CDH-Ca was washed with deionized water. 2+ Afterwards, it was immersed in EDC / NHS solution for 1-10 min to obtain appropriate chemical cross-linking.
8. The use of a 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel in corneal regeneration as claimed in claim 1 or 2, characterized in that: Growth factors that promote corneal re-epithelialization and histone deacetylase inhibitors were added to the polymer ink of gelatin / dihydrazide carbonate modified sodium alginate to obtain two types of printing bio-inks. The 3D printed bioactive double-layer hydrogel scaffolds were obtained by layer-by-layer printing using a multi-nozzle printing system, and then enhanced by soaking them in calcium chloride aqueous solution and EDC / NHS aqueous solution in turn to achieve cross-linking.
9. The use of a 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel in corneal regeneration according to claim 8, characterized in that: Growth factors that promote corneal re-epithelialization include epidermal growth factor, keratinocyte growth factor or fibroblast growth factor. The concentration of growth factors that promote corneal re-epithelialization is 1-5 μg / ml.
10. The use of a 3D printed high-strength gelatin / dihydrazide carbonate modified sodium alginate natural polymer hydrogel in corneal regeneration according to claim 8, characterized in that: The histone deacetylase inhibitor is trichostatin A or vorinostat, and the concentration of the histone deacetylase inhibitor is 1-5 μmol / L.
Citation Information
Patent Citations
Three-dimensional bioprinted artificial cornea
CN107106734A
Method for preparing hydrogel wound dressing through low-temperature biological 3D printing technology
CN109731130A
Tissue-engineered cornea and preparation method thereof
CN110613862A
3D printing bionic corneal limbal graft as well as preparation method and application thereof
CN115671398A
Three-dimensional bioprinted artificial cornea
WO2016049345A1
Cited By
Bionic layered cornea repair gel as well as preparation method and application thereof
CN121910947A